Injuries of the trochanteric region: can analysis of radiographic indices help in prediction of recurrent osteoporotic hip fractures? - Pellegrini, Andrea; Tacci, Fabrizio; Leigheb, Massimiliano; Costantino, Cosimo; Pedrazzini, Alessio; Pedrazzi, Giuseppe; Vaienti, Enrico; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2017)
Objective: In a context of bone fragility, primitive and subsequent fractures are a growing problem in the industrialized countries where the mean age of the population is constantly increasing. Among the various factors that favor a fragility fracture, the most important is osteoporosis, a pathology that can be prevented through diagnostic screenings and treated by pharmacological and rehabilitative therapies. The aim of this study is to identify the subjects who are likely to have a higher risk of subsequent fractures of the trochanteric region through a retrospective radiographic evaluation of patients affected by low-energy trochanteric fractures and operated by intramedullary fixation between June 2013 and June 2015, so they can be targeted for prevention interventions. Materials and Methods: Three hundred and sixty-one patients yet alive were analyzed 2 years after surgery. Fifty-one (group 1), characterized by another contralateral trochanteric femoral fracture, were included. All subjects were retrospectively examined with the analysis of contralateral femur X-ray performed at the time of initial trauma in order to detect a condition of bone fragility and a predisposition to fractures by evaluating three radiographic indices (Singh index, Dorr’s classification and Cortical Thickness Index). Patients of group 1 were compared to the other 310 patients (group 2) affected by isolated trochanteric fracture. Results: Group 1 had all radiographic indices worse than group 2. Conclusions: The results observed suggest that orthopedists can use radiographic indices, in particular Cortical Thickness Index, as a valuable, simple and inexpensive screening tool for prevention of recurrent osteoporotic fractures.